White coat and masked effects depend on blood pressure level and time of blood pressure measurement - Halfon, Matthieu; Taffe, Patrick; Wuerzner, Gregoire (Frontiers in Medicine, 2025)
BackgroundA total of 24 h ambulatory blood pressure monitoring (ABPM) offers enhanced accuracy for evaluating true blood pressure and associated risks compared to office blood pressure (OBP). However, conflicting results have been reported in studies comparing the two settings, largely due to the statistical bias introduced by the mean difference calculation using the Bland and Altman method, especially if the inherent circadian variation of blood pressure is not considered. This study aimed to assess the difference between OBP and ABPM using a refined statistical approach while accounting for circadian variations at different blood pressure levels.MethodsMultilevel/mixed-effects harmonic regression models were employed to estimate mean 24 h systolic and diastolic blood pressure profiles. The bias plot method, with ABPM as the reference, was used to calculate the OBP- daytime ABPM difference.ResultsA total of 647 participants were included with a median of 63 measurements per individual, with most OBP measurements conducted between 8 a.m. and 10 a.m. Analysis showed individual average systolic OBP-ABPM differences ranging from +10 to −30 mmHg and diastolic differences ranging from +20 to −60 mmHg. As ABPM values increase, the patients tend to exhibit a masked effect. Normotensive individuals on ABPM exhibited a white coat effect phenotype, with systolic OBP-ABPM differences ranging from +6 to +9 mmHg. Conversely, hypertensive patients displayed a modest white coat effect for those at the lower hypertension limit and a pronounced masked effect for those at higher hypertension levels. The reduced circadian blood pressure variation observed in hypertensive patients, characterized by a nadir shift to later in the day, contributed to this divergence.ConclusionDifferences between OBP and ABPM depend on mean ABPM blood pressure levels. OBP tends to overestimate in normotensive and underestimate in hypertensive patients. Differences in circadian variation between these groups contribute to the variance.